Antimicrobial Peptides and Cell-Penetrating Peptides for Treating Intracellular Bacterial Infections - Buccini, Danieli F.; Cardoso, Marlon H.; Franco, Octavio L. (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial infections caused by intracellular pathogens are difficult to control. Furthermore, conventional antibiotics therapies are often ineffective, as high doses are needed to increase the number of antibiotics that will cross the host cell membrane to act on the intracellular bacterium. Moreover, higher antibiotics doses may lead to elevated severe toxic effects against host cells. In this context, antimicrobial peptides (AMPs) and cell-penetrating peptides (CPPs) have shown great potential to treat such infections by directly acting on the intracellular pathogenic bacterium or performing the delivery of cargos with antibacterial activities. Therefore, in this mini-review, we cover the main AMPs and CPPs described to date, aiming at intracellular bacterial infection treatment. Moreover, we discuss some of the proposed mechanisms of action for these peptides classes and their conjugation with other antimicrobials.